2019
DOI: 10.7759/cureus.5195
|View full text |Cite
|
Sign up to set email alerts
|

Advance Rectal Cancer in a Young Patient: Should Screening Start Early?

Abstract: Colorectal cancer is the third most common non-cutaneous malignancy in the United States, and the second most common cause of cancer-related deaths. Colorectal cancer is a broad term to include both colon and rectal cancer. Rectal cancer is commonly seen in age more the 50 years and often present with rectal bleeding. In this article, we will be discussing about a young female patient who presented with somatic pain as an initial symptom for metastatic rectal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The same is true for patients with rectal cancer. However, in the last decade, the incidence of rectal cancer has increased exponentially in patients less than 50 years of age, even without a family history of colorectal cancer [38]. To further clarify the causes of this phenomenon and identify potential prevention and early detection strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for patients with rectal cancer. However, in the last decade, the incidence of rectal cancer has increased exponentially in patients less than 50 years of age, even without a family history of colorectal cancer [38]. To further clarify the causes of this phenomenon and identify potential prevention and early detection strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological studies have shown that within this age group are more prevalent mucinous, less differentiated intestinal tumors with poor prognosis making debatable the idea to lower the screening age for CRC with preventive colonoscopy [ 7 , 8 ]. Late detection is usually associated with advanced stage of CRC in young patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%